Self-Nanoemulsifying Drug Delivery System-Containing the Poorly Absorbed Drug – Valsartan in Post-Bariatric Surgery - Huang, Tzu-Hao; Chen, Chih-Jung; Lin, Hsin-Chia Angela; Chen, Chun-Han; Fang, Jia-You (International journal of nanomedicine, 2023)
Morbid obesity and its related metabolic syndrome are an important health issue. Recently, sleeve gastrectomy (SG) and Roux-en-Y gastric bypass (RYGB) have accounted for the most popular bariatric surgeries. Valsartan (VST) is a common hypertension drug, and nano-carriers can increase its solubility and bioavailability. This study aims to explore the nano-VST formula in bariatric surgery subjects. High-fat fed animals were used as obese models. Operations were performed according to a standardized protocol. The drug was administrated by gavage, and blood samples were taken by serial tail vein sampling. Caco-2 cells were used for examining cell viability and drug uptake. A self-nano-emusifying drug delivery system (SNEDDS) formula was composed of sefsol-218, RH-40 and propylene glycol by a specified ratio, while high-performance liquid chromatography (HPLC) was used for determining drug concentrations. Post-operatively, subjects that underwent RYGB lost more body weight compared to the SG group. The SNEDDS did not exhibit cytotoxicity after adequate dilution, and the cytotoxicity was not related to VST dose. A better cellular uptake of SNEDDS was observed in vitro. The SNEDDS formula achieved a diameter of 84 nm in distilled water and 140 nm in simulated gastric fluid. In obese animals, the maximum serum concentration (C ) of VST was increased 1.68-folds by SNEDDS. In RYGB with SUS, the C was reduced to less than 50% of the obese group. SNEDDS increased the C to 3.5 folds higher than SUS and resulted in 3.28-folds higher AUC in the RYGB group. Fluorescence imaging also confirmed a stronger signal of SNEDDS in the gastrointestinal mucosa. SNEDDS accumulated a higher drug concentration than suspension alone in the liver of the obese group. SNEDDS could reverse the VST malabsorption in RYGB. Further studies are mandatory to clarify post-SG change of drug absorption.